Discourse markers and world Englishes. Issue 4 (11th March 2021) - Leuckert, Sven; Rüdiger, Sofia
Abstract: In this introduction to the special issue Discourse markers and world Englishes, we briefly introduce our definition of discourse‐pragmatic markers (by all means contentious items to define) and give a short overview of previous research on discourse markers in world Englishes. As the main bulk of previous research in this field has been based on material from Inner Circle Englishes, the aim of this collection of articles is twofold: (1) to provide insight into underresearched varieties of English; and (2) to investigate underresearched discourse‐pragmatic items. Discourse markers are not only a powerful means to index social meaning and carry a wide range of functions, they are also indicative of 'glocalisation'. As such, discourse‐pragmatic items can provide important input to the modelling of world Englishes in general and the description of individual varieties specifically.